2021
DOI: 10.1371/journal.pone.0246271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived social support on psychological distress and life satisfaction among Nepalese migrants in Japan

Abstract: Background The world is becoming individualized due to modernization. International migration is one of the factors that lead to family dissociation and a lack of social support. Social support is viewed as a crucial factor that contributes to psychological well-being and satisfaction with life among migrants. However, very little is known about the impacts of social support on psychological distress and satisfaction with life among migrants. Therefore, we conducted this study to assess the association of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…These findings support a previous study by Permatasari et al (2021), which stated that family and other close parties positively contribute to students' well-being during online learning and help build academic resilience during online learning. Furthermore, the analysis also showed that there is a significant relationship between peer support and the support of other close individuals (r = 0.565, p <0.01), in line with the findings by Khatiwada et al (2021). This finding further indicates a strong relationship between these two sources of social support.…”
Section: The Relationship Between Respondents' Sociodemographic Background and Social Supportsupporting
confidence: 84%
“…These findings support a previous study by Permatasari et al (2021), which stated that family and other close parties positively contribute to students' well-being during online learning and help build academic resilience during online learning. Furthermore, the analysis also showed that there is a significant relationship between peer support and the support of other close individuals (r = 0.565, p <0.01), in line with the findings by Khatiwada et al (2021). This finding further indicates a strong relationship between these two sources of social support.…”
Section: The Relationship Between Respondents' Sociodemographic Background and Social Supportsupporting
confidence: 84%
“…Moreover, its risk is even higher for retired people [44] that was over de 80% of our sample. Another problem in our solution was the high correlations between the three-factor (0.700 to 0.929), that were superiors than those informed in previous studies that endorsed the 3-factors model [17,20,24,30,35], but similar to the correlations reported in Nigerian teenagers, were they were from 0.80 to 0.95 [25]. The highest correlation was between Family's and Significant others' factors, putting in doubt it those factors are distinguishable, or it is best a solution the 2-factors solution (Model C), as has been found in the first study with this MSPSS adaptation [3].…”
Section: Discussionmentioning
confidence: 86%
“…This version modifies answer options. In 1988, Zimet changed the 5-point Likert scale of this original version for a 7point scale (1 = very strongly disagree to 7 = very strongly disagree) to increase responser variability and minimize a ceiling effect (Zimet), but in published studies, we can find both 5-point [9,19,21] of 7-point scale versions [23,24,26,[32][33][34][35]. All of them from a stronger disagreement to a stronger agreement.…”
Section: Validation Of the Mspssmentioning
confidence: 99%
“…Using Google forms, a link to an invitation to participate was sent to the targeted population on these social networks. A “chain referral” recruitment strategy ( Khatiwada et al., 2021 ) was promoted, in which each participant was encouraged to share contacts and roll out the survey invitation link to as many participants as desired. Therefore, the link was further shared with potential respondents apart from the first point of contact, and so on.…”
Section: Methodsmentioning
confidence: 99%